Representação de sonhos e metáfora onírica na arte: o virtual do analógico ao digital - Almeida, Larissa Paes de (2021)
This study investigates the representation of dreams in the form of oneiric metaphors in the visual arts and in literature, considering the transformations brought about within this genre by artists making use of technologies of the emergent digital media. Based on the assumption that dreams are the manifestation of the structures of the unconscious, the study first presents a general panorama and bibliographical survey of the genre of dream art and discusses exemplary works that have represented dreams in literature, painting, and cinema. Next, it presents the emergent technology of Virtual Reality (VR) that have recently been applied in these arts, investigating the potential of this media for expanding the expressive potential of the genre. The author argues that the new technologies of Virtual Reality are predestined for being applied in dream art. They do not only extend the mediatic potential of the genre but also succeed in reducing the distance between real dreams and their representation in the genre of dream art. The concept of cyberspace is indicative of the new potentials to create the imaginary aura characteristic of oneiric states of consciousness